Association between sexting and sexual coercion among female adolescents. (December 2016) - Choi, HyeJeong; Van Ouytsel, Joris; Temple, Jeff R.
Abstract: This study aims to investigate whether experiences of offline sexual coercion are associated with adolescent females' involvement in different types of sexting behaviors. It draws on data from 450 ethnically diverse female adolescents with an average age of 19.02 years ( SD = 0.74) who were originally recruited in southeast Texas. The participants were asked about their experiences with sexual coercion, and their engagement in sexting behavior (i.e., sending, requesting, and being asked for a sext, and receiving a sext without giving permission). Logistic regressions were used to analyze these relationships, while controlling for age, ethnicity, education level, living situation, and sexting behaviors in the year prior of the study. Offline sexual coercion was significantly associated with sending and being asked for a naked image, as well as receiving a naked image without giving permission. The results suggest that sexting could function as an online extension of offline forms of sexual coercion.